Clinical features of dengue hemorrhagic fever and risk factors of shock event - Rismala Dewi; Alan Roland Tumbelaka; Damayanti Rusli Sjarif (Indonesian Pediatric Society, 2006)
Background Dengue hemorrhagic fever (DHF) can lead to highmorbidity and mortality. Its clinical features vary from time to time.Many studies were performed to determine the risk factors of se-vere dengue infection.Objective To find out clinical features and risk factors for predict-ing the likelihood of shock in DHF.Methods A retrospective cohort study was conducted in all con-firmed DHF children who were hospitalized at the Department ofChild Health, Cipto Mangunkusumo Hospital within the period ofJanuary 1, 2003 until June 30, 2004. Risk factors for developmentof shock were analyzed using chi-square test and multiple logisticregressions with a level of significance of <0.05.Results A total of 101 patients, consisted of 47 males and 54females were enrolled in this study. Mean age was 6.5 (SD 3.6)years, ranged from 5 months to 15 years. About 31.7% patientshad grade III DHF, 30.7% grade II, and 26.7% grade IV (including1 patient with encephalopathy). Shock was more frequent amongpatients aged between 6-10 years, female, under-nourished, bodytemperature <38Â°C, hematocrit level 46-50 vol%, and platelet count<20 000/ml. During year 2003-2004, there was increased numberof patients who developed shock. Based on univariate analysis,hepatomegaly, high hematocrit value, and thrombocytopenia wereconsidered significantly different. Among those variables analyzedwith multiple logistic regression method, only hepatomegaly andthrombocytopenia were identified as predictors of shock.Conclusion There was an alteration on clinical features of DHFin our hospital in 2003-2004 period compared to the previous years.Hepatomegaly and platelet count <50 000/ml are independent riskfactors of shock among DHF patients